Implementation of Circuit Wizard Software in Basic Electronics Course to Improving Student Motivation and Learning Outcomes - Yanti Sofi Makiyah; Ihsan Nurdiansah; Ifa Rifatul Mahmudah; Rifa’atul Maulidah (Universitas Muhammadiyah Purworejo, 2022)
All physics education student must take Basic Electronics courses at Siliwangi University. The course teaches students how to create electronic components. Due to the Covid-19 pandemic, the unprecedented shift from classroom learning to online learning has profoundly impacted levels of students’ learning motivation and learning outcomes in introductory electronics course online laboratory activities. The quantitative descriptive method research was conducted to analyze the implementation of the Circuit Wizard application on students’ learning motivation and learning outcomes in the introductory electronics course on the logic gate topic. Students who had recently completed the logic gate simulation were asked to write up a simulation results report. The report was used to measure students' learning outcomes. At the same time, an online questionnaire was administered to measure students’ motivation. Data were collected from 46 students of physics education (fifth and seventh semesters, the academic year 2021/2022). The results revealed students' motivation was as follows: 45% were in the good category, 27% were in a low category, and 28% were a low motivation. Findings also revealed student learning outcomes identified: 35% got an A grade, 33% got a B grade, and 4% got a C grade. These findings suggested that the implementation of Circuit Wizard in basic electronics courses positively impacted students’ learning motivation and learning outcomes.